Uterus infantilis: a novel phenotype associated with AARS2 new genetic variants. A case report - Kazakova, Ekaterina; Téllez-Martínez, José Alberto; Flores-Lagunes, Leonardo; Sosa-Ortiz, Ana Luisa; Carillo-Sánchez, Karol; Molina-Garay, Carolina; González-Domínguez, Carlos Alberto; Jimenez-Olivares, Marco; Fernandez-Valverde, Francisca; Vargas-Cañas, Edwin Steven; Vázquez-Memije, Martha Elisa; Garcia-Latorre, Ethel Awilda; et al. (Frontiers in Neurology, 2023)
Objectives To report the first Mexican case with two novel AARS2 mutations causing primary ovarian failure, uterus infantilis, and early-onset dementia secondary to leukoencephalopathy. Methods Detailed clinical, clinimetric, neuroimaging features, muscle biopsy with biochemical assays of the main oxidative phosphorylation complexes activities, and molecular studies were performed on samples from a Mexican female. Results We present a 41-year-old female patient with learning difficulties since childhood and primary amenorrhea who developed severe cognitive, motor, and behavioral impairment in early adulthood. Neuroimaging studies revealed frontal leukoencephalopathy with hypometabolism at the fronto-cerebellar cortex and caudate nucleus. Uterus infantilis was detected on ultrasound study. Clinical exome sequencing identified two novel variants, NM_020745:c.2864G>A (p.W955*) and NM_020745:c.1036C>A (p.P346T, p.P346Wfs*18), in AARS2. Histopathological and biochemical studies on muscle biopsy revealed mitochondrial disorder with cytochrome C oxidase (COX) deficiency. Conclusions Several adult-onset cases of leukoencephalopathy and ovarian failure associated with AARS2 variants have been reported. To our best knowledge, none of them showed uterus infantilis. Here we enlarge the genetic and phenotypic spectrum of AARS2-related dementia with leukoencephalopathy and ovarian failure and contribute with detailed clinical, clinometric, neuroimaging, and molecular studies to disease and novel molecular variants characterization.